Effect of synthesis parameters on catalytic performance of Fe/Ti-PILC catalysts for SCR-C3H6 and in situ DRIFTS study. Issue 6 (December 2020) - Wen, Nini; Dong, Shilin; Su, Yaxin; Deng, Wenyi; Zhao, Bingtao
Graphical Abstract: Highlights: Iron-based catalysts supported on Ti-pillared clays were prepared for SCR-C3 H6 . Ti/clay ratio was the dominant synthesis parameters to influence SCR activity. 100% NO conversion was proved at 400 °C when Ti/clay ratio was 10. Ti/clay ratio promoted the amount of Lewis acid sites. In situ DRIFTS results indicated R-NCO species were important intermediates. Abstract: A series of iron ion-exchanged TiO2 - pillared clay catalysts (19Fe/Ti-PILC- x - y ) were synthesized and evaluated for the performance of selective catalytic reduction of NO with propene (SCR-C3 H6 ). The effect of the Ti/clay ratio and the calcination temperature on the catalytic performance was investigated. Results showed that the maximum NO conversion reached almost 100% at 400 °C, when the Ti/clay ratio was 10. The calcination temperature of the support had a very slight effect on the SCR performance. Several techniques of XRD, N2 adsorption/desorption, Py-FTIR, etc. were used to characterize the catalysts. The Ti/clay ratio and calcination temperature led to an effect on the TiO2 crystallites, further influencing the structure of TiO2 pillared clay. Metal oxides (TiO2, Fe2 O3 ) were well-dispersed on these catalysts. An appropriate Ti/clay ratio obviously promoted the amount of Lewis acid, which is the dominant acidity on the catalyst surface and is the critical factor to influence the SCR activity. In situ DRIFTS studies revealed that monodentate nitrates, bidentate nitrates, formates, acetates, and isocyanates (R-NCO) were the main active species on the catalyst surface, where these nitrates promoted the oxidation of C3 H6 to formats and acetates, and the R-NCO species were the important intermediates in the reaction of C3 H6 -SCR.